CHARACTER EDUCATION TO ENHANCE SANTRI"™S SELF CONTROL: IMPLEMENTATION AND CHALLENGES - Sudrajat, Sudrajat; Islah, Islah; Shodiq, Muhamad Fajar (Jurnal Visi Ilmu Pendidikan, 2024)
This study aimed to analyze the implementation and associated challenges of character education in Al-Mukmin Islamic Boarding School, with a specific focus on its integration into the curriculum. Utilizing a descriptive qualitative methodology, the research involved a thorough examination of educational practices, guided by data collected through document analysis, observations, and semi-structured interviews with teachers and students. The data analysis, conducted through thematic analysis, shed light on how character education is structured and the myriad challenges that emerge in its execution. Key findings reveal that while Al-Mukmin Islamic Boarding School adopts a comprehensive approach to character education, encompassing learning, habituation, and practice, it concurrently grapples with significant hurdles. These include the scarcity of qualified educators proficient in both academic and moral teachings, the need to balance academic rigor with moral values, cultural influences affecting educational practices, and the complexities of engaging students and assessing moral development effectively. These insights not only highlight the intricacies of embedding character education in Islamic boarding schools but also underscore the necessity for tailored strategies to surmount these challenges, thereby contributing valuable perspectives to the field of educational research.